Risk Factors and Outcomes Associated with Blunt Cerebrovascular Injury in Patients with Mild or Moderate Traumatic Brain Injury. (16th November 2020) - Hoffman, Haydn; Bunch, Katherine; Protas, Matthew; Chin, Lawrence S
Abstract: INTRODUCTION: Blunt cerebrovascular injury (BCVI) represents a spectrum of traumatic injuries to the carotid and vertebral arteries that is an often-overlooked source of morbidity and mortality. It has not been studied iin patients with mild or moderate traumatic brain injury (mTBI) independently. METHODS: The National Trauma Data Bank from 2013 to 2017 was queried to identify patients with mTBI who suffered blunt injuries. BCVI was identified using Abbreviated Injury Scores and included blunt carotid artery injury (BCAI) and blunt vertebral artery injury (BVAI). A binary logistic regression was used to identify patient- and injury-related factors associated with BCVI. Binary logistic regressions were also performed to evaluate the effect of BCVI on stroke, in-hospital mortality, non-routine discharge disposition, total length of stay (LOS), intensive care unit (ICU) LOS, and number of days mechanically ventilated. RESULTS: Out of 485, 880 patients with mTBI there were 4, 382 (0.9%) with BCVI. Cervical spine fracture was the strongest predictor of BCAI (OR 1.97, 95% CI 1.77-2.19), followed by mandible fracture and basilar skull fracture. Cervical spine fracture was also the strongest predictor of BVAI (OR 18.28, 95% CI 16.47-20.28), followed by spinal cord injury and neck contusion. Stroke was more common in patients with BCAI (OR 5.50, 95% CI 4.19-7.21) and BVAI (OR 7.238, 95% CI 5.929-8.836). BVAI, but not BCAI increased the odds of mortality. Both were associated with non-routine discharge and increased LOS, ICU LOS, and number of days mechanically ventilated. CONCLUSION: The incidence of BCVI in patients with mTBI is low, and it usually does not require invasive treatment. However, it is associated with greater odds of stroke and negative outcomes.